Bestand der Dinge – A summer school as a condensed approach to teaching and learning (EAAE Annual Conference Proceedings, 2024)
The summer school “Bestand der Dinge”, which took place in Berlin in September 2023, introduced a novel approach that went beyond the traditional academic context. It was the result of a collaboration between baunetz CAMPUS, the German online portal for the academic world of architecture, and Prof. Jan Kampshoff of the Technical University of Berlin. With 30 students from various German and Austrian universities in attendance, the summer school challenged participants to explore the intricacies of working with the existing built fabric – an aspect that is often overlooked in the curricula of architecture schools. Positioning itself at the intersection of architectural production and its critical communication, it opened a space for negotiating pressing issues within the discipline and explored the role of architecture in a world where transformation rather than new construction is the primary goal. A variety of teaching methods and the expertise of numerous guests and mentors enhanced the learning experience. The paper discusses the potential of such a condensed format to catalyze change and elaborates on the main questions posed and on the teaching methods used. The baunetz CAMPUS summer school will become an annual event, with the next iteration scheduled for September 2024 in Wuppertal.